Relationship between kinematic variables of jump throwing and ball velocity in elite handball players - Akl, A.-R.; Hassan, I.; Hassan, A.; Bishop, P. (Applied Sciences, 2019)
The purpose of this pilot study was to evaluate the relationship between the kinematic variables of the right hand and left leg with ball velocity during jump-throwing phases in handball for better-informed training. We investigated ball velocity and the key kinematic variables of jump throwing during different throwing phases in three strides. Ten right-handed male handball professional players who had competed in the Egyptian Handball Super League participated in this study. Jump throwing performance was divided into three phases (cocking, acceleration and follow-through), which included eight events during the throwing. Five trials were captured for each player, and a 3D analysis was performed on the best trial. Results indicated that the velocity of the throwing hand was the most important variable during jump throwing, which was correlated with ball velocity during the three phases of performance in four events: Initial contact (IC) (r = 0.66*), initial flight (IF) (r = 63*), maximum height of the throwing hand (Max-HH) (r = 0.78*) and ground contact (GC) (r = 0.83*). In addition, the initial flight was the most important event in which players need to be using the best angles during performance, particularly the shoulder angle